SCI1 Is a Direct Target of AGAMOUS and WUSCHEL and Is Specifically Expressed in the Floral Meristematic Cells - Cruz, Joelma O.; San Martin, Juca A. B.; Lubini, Greice; Strini, Edward J.; Sobral, Rómulo; Pinoti, Vitor F.; Ferreira, Pedro B.; Thomé, Vanessa; Quiapim, Andréa C.; Dornelas, Marcelo C.; Pranchevicius, Maria Cristina S.; Madueño, Francisco; et al. (Frontiers in Plant Science, 2021)
The specified floral meristem will develop a pre-established number of floral organs and, thus, terminate the floral meristematic cells. The floral meristematic pool of cells is controlled, among some others, by WUSCHEL (WUS) and AGAMOUS (AG) transcription factors (TF). Here, we demonstrate that the SCI1 gene, a cell proliferation regulator, starts to be expressed since the floral meristem specification of Nicotiana tabacum and is expressed in all floral meristematic cells. Its expression is higher in the floral meristem and the organs being specified, and then it decreases from outside to inside whorls when the organs are differentiating. SCI1 is co-expressed with NtWUS in the young floral meristem and the whorl primordia at stage -7. Later in development, SCI1 is co-expressed with NAG1 (N. tabacum AG) in the floral meristem and specialized tissues of the pistil. In silico analyzes identified cis-regulatory elements for these TFs in the SCI1 genomic sequence. Y1H and EMSA demonstrated that both TFs interact with the SCI1 promoter sequence. Additionally, the luciferase activity assay showed that NAG1 clearly activates SCI1 expression, while it indicated that NtWUS might act to repress SCI1 expression. Taken together, our results suggest that during floral development, the spatiotemporal regulation of SCI1 by NtWUS and NAG1 may result in the maintenance or termination of proliferative cells in the floral meristem.